A Predictive Model of Organizational Commitment: The Role of Organizational Culture and Agile Leadership - Rosada, Rosada; Adam, Abdulhamid (Asosiasi Asesmen Pendidikan (AAP), 2026)
Teachers’ organizational commitment is an important factor in maintaining performance quality, loyalty, and the sustainability of educational processes in schools. However, the level of teachers’ commitment often varies in practice, highlighting the need to understand the factors that can enhance it. This study aims to analyze the influence of organizational culture and agile leadership on teachers’ organizational commitment. A quantitative approach was employed using the SEM-PLS analysis method. Data were collected through questionnaires distributed to teacher respondents and analyzed to examine the relationships among variables in the research model. The results show that agile leadership has a positive and significant effect on organizational commitment, with a path coefficient of 0.181, a t-statistic of 3.047, and a p-value of 0.002. In addition, organizational culture also has a positive and significant effect on organizational commitment, with a path coefficient of 0.699, a t-statistic of 11.519, and a p-value of 0.000. These findings indicate that stronger implementation of agile leadership and a well-established organizational culture contribute to higher levels of teachers’ organizational commitment. Therefore, strengthening organizational culture and implementing adaptive leadership are important strategies to enhance teachers’ commitment within educational institutions.